2015
DOI: 10.1186/s40623-015-0312-1
|View full text |Cite
|
Sign up to set email alerts
|

TEC prediction performance of the IRI-2012 model over Ethiopia during the rising phase of solar cycle 24 (2009–2011)

Abstract: This paper discusses the performance of the latest version of the International Reference Ionosphere (IRI-2012) model for estimating the vertical total electron content (VTEC) variation over Ethiopian regions during the rising phase of solar cycle 24 (2009-2011). Ground-based Global Positioning System (GPS) VTEC data, inferred from dual-frequency GPS receivers installed at Bahir Dar (geographic latitude 11.6°N and longitude 37.35°E, geomagnetic latitude 2.64°N and longitude 108.94°E), Nazret (geographic latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Kumar on the other hand, showed that the IRI-2012 model overestimates the measured VTEC during low and high solar activity phases in equatorial regions [4]. However, in the Ethiopian region, Tariku stated that the model performed better during low solar activity when compared to high solar activity [27,28]. Elmunim investigated the performance of the IRI-2012 model in Langkawi, Malaysia [29].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar on the other hand, showed that the IRI-2012 model overestimates the measured VTEC during low and high solar activity phases in equatorial regions [4]. However, in the Ethiopian region, Tariku stated that the model performed better during low solar activity when compared to high solar activity [27,28]. Elmunim investigated the performance of the IRI-2012 model in Langkawi, Malaysia [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous ionospheric studies have shown that the IRI 2012 model data for the equatorial ionosphere of the African longitude sector have a good correlation with measured data. For example, Tariku () showed that the IRI‐2012 model with the NeQuick topside option was generally good in estimating the total electron content derived from GPS measurements.…”
Section: Ray Tracing Simulationmentioning
confidence: 99%
“…Comparing ionospheric model estimations to real-time experimental data (from equipment) is a prevalent approach used by ionospheric researchers to assess model accuracy and validate them for useful applications (Migoya-Orué et al, 2008;Rabiu et al, 2014;Tariku, 2015;Cherniak and Zakharenkova, 2016;Okoh et al, 2018;Sharma et al, 2018). Researchers (Ezquer et al, 2018;Okoh et al, 2018;Teriku, 2020) conducted a comparison of different ionospheric TEC models (IRI, IRI-plas, and NeQ-2) using GNSS measurements and concluded that NeQ-2 performs better than other models regardless of time or location.…”
Section: Introductionmentioning
confidence: 99%